2018
DOI: 10.1515/ract-2017-2867
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of rare earth elements, Th and U profile of a site for a potential coal based power plant by instrumental neutron activation analysis

Abstract: To study the compositional trends of rare earth elements (REEs: La, Ce, Nd, Sm, Eu, Tb, Dy, Yb, Lu), Th and U in soil samples collected from a site for a potential coal based power plant as well as to conduct a preliminary assessment of environmental impact of the proposed power plant in terms of REEs, Th and U, we have analyzed nine soil samples by instrumental neutron activation analysis. Evaluation of data quality by repeated analysis of IAEA-Soil-7 and IAEA-SL-1 ensures a proper data base-line for the REEs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…, kaolinite and illite). 14,77,81 Aside from this, a very high correlation between typical lithophile elements Th and U ( r = 0.886; p < 0.01) (Table S5†) in this study demonstrated similar sedimentary characteristics and was hypothesized to be governed by wave hindering heavy minerals, namely monazite [(La, Ce, Nd, Th) PO 4 ] (Th-rich mineral) and zircon (ZrSiO 4 ) (U-rich mineral). 1,82 As a result, in an oxidizing environment, Th is weather-resistant (remains as insoluble Th 4+ ), but U transforms into a soluble oxyanion-complex (UO 2 ) and may easily be depleted from sediment by leaching and/or weathering.…”
Section: Resultssupporting
confidence: 69%
“…, kaolinite and illite). 14,77,81 Aside from this, a very high correlation between typical lithophile elements Th and U ( r = 0.886; p < 0.01) (Table S5†) in this study demonstrated similar sedimentary characteristics and was hypothesized to be governed by wave hindering heavy minerals, namely monazite [(La, Ce, Nd, Th) PO 4 ] (Th-rich mineral) and zircon (ZrSiO 4 ) (U-rich mineral). 1,82 As a result, in an oxidizing environment, Th is weather-resistant (remains as insoluble Th 4+ ), but U transforms into a soluble oxyanion-complex (UO 2 ) and may easily be depleted from sediment by leaching and/or weathering.…”
Section: Resultssupporting
confidence: 69%
“…Bangladesh is undergoing rapid industrialization with gradually evolving environmental legislation, just like other emerging nations throughout the world. The greatest mangrove forest is in Rampal, a southern region of Bangladesh, where a coal-fired power plant has been planned to be developed. , The environment surrounding the power plant location includes soil as a key element. For the evaluation of upcoming pollution problems, a substantial number of industrial establishments are expected to be built at Rampal in addition to the coal-based power station.…”
Section: Introductionmentioning
confidence: 99%
“…Tb and Yb concentrations were found to be 0.05±0.01 and 0.41±0.03 respectively. The assessment of the content of Th and U is essential from a radiological standpoint, since it indicates the radioactive influence on coastal marine sediments [22]. In the Quseir harbour area, the average concentrations of U and Th were 2.8±0.26 mg/kg and 0.26±0.02 mg/kg, respectively.…”
Section: Resultsmentioning
confidence: 99%